Use of Comet Assay in Human Lymphocytes as a Molecular Biomarker for Simultaneous Monitoring of Genetic Damage and Genotoxicity in Residents Who Lived Nearby the Santiago River, Mexico, in 2012 - Monica Reynoso-Silva (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2015)
Most aquatic  and  health  management  authorities  need  assessing  the  potential genotoxicity of contaminated effluent to avoid the effects of a lot chemical agents found as environmental contaminants.Previous studies report the presence of some pesticides and heavy metals in waters of Santiago River and suggest a genetic risk for residents, who lived nearby this river, so it is important determine its mutagenic risk. The objective of this study was to use of comet assay in human lymphocytes as a molecular biomarker of genetic damage in residents who lived nearby the Santiago River, México, in 2012 and monitoring simultaneous of genotoxicity of these waters in unexposed persons.The genotoxic activity of water samples taken from the Santiago River was evaluated in human lymphocytes from persons unexposed and the evaluation of genetic damage were studied in people living near the river.The results indicated the existence of mutagens in the water (p ≤ 0.05), genetic damage statistically significant (p ≤ 0.05) in residents who lived nearby the Santiago River and carcinogenic risk to human health.The comet assay system in human lymphocytes can be used as a molecular biomarker for simultaneous monitoring of genetic damage and genotoxicity in aquatic environments contaminated with genotoxic, additionally this bioassay is reliable and inexpensive